The Risk Factor that Affect Children Diarrhea in The Island of Java 2013 (Riskesdas 2013 Data Analysis) - Sari, Dian Perwita; Budyanra, Budyanra (Journal of Educational, Health and Community Psychology, 2017)
Abstract  Diarrhea is the biggest cause of infant and child death in Indonesia. In 2013, Indonesian Ministry of Health stated that children diarrhea incidence was still high and rated as public health problem accounting for 6.7 per cent. Two of five provinces with the highest incidence of infant diarrhea in Indonesia was located in the island of Java, even though Java has the biggest achievement in infant and child healthcare coverage as well as the physical quality of drinking water and improved sanitation over the national. Based on these facts, the purpose of this study was to identify risk factors that affect the incidence of children diarrhea in Java 2013. Binary logistic regression was used to statistical analysis with incidence of children diarrhea as response variable while the explanatory variables are age, nutritional status, level maternal education, maternal age, maternal behavior of washing hands, access to sources of drinking water, access to sanitation facilities and household density. The source of data was Riskesdas 2013. The results of this study showed that all the explanatory variables: age, nutritional status, maternal education level, maternal age, maternal behavior of washing hands, access to sources of drinking water, access to sanitation facilities and household density significantly affect the incidence of children diarrhea. Keywords: children diarrhea, binary logistic regression, Riskesdas 2013.